Enhance in-vitro rumen fermentation of Panicum maximum with biological supplements - Sumudu Chathurika; Sathya Sujani; Ariyathilaka Manawadu; Thakshala Seresinhe (Jurnal Ilmu Ternak dan Veteriner, 2019)
Recently the utilization of biological feed additives over chemical feed additives in animal feeds have increased. The objective of the present study was to evaluate the effect of supplementing wild guinea grass (panicum maximum) with two plant species, artocarpus heterophyllus (jack leaves; ah) and tridax procumbens (Tp) containing plant secondary metabolites tannin and saponin, respectively and the enzyme product dyadic cellulase (Ce) and yeast (Ye). For each suplement two levels of treatments were tested. In plant-based suplements 20 (Aht1, Tpt1) and 30% (Aht2 and Tpt2) substituted the base substrate. The enzyme was applied as 10 µl (Cet1) and 20 µl (Cet2) and yeast as 4 mg (Yet1) and 6 mg (Yet2). the experimental design was a randomized complete block design (rcbd) and the period of in vitro rumen fermentation incubation was 72 hrs. All treatments significantly (P < 0.05) enhanced the in vitro gas production (Ivgp) compared with the control. Treatments of ah and ce significantly (P < 0.05) improved the in vitro rumen dry matter degradability (ivrdmd). All treatments significantly (P<0.05) suppressed the ruminal protozoa population as compared to the control. Ammonia nitrogen (Nh3-N) production was not significantly (P>0.05) influenced with supplements. in conclusion, treatments enhanced the rumen fermentation in means of enhanced ivgp, ivrdmd and reduced protozoa numbers.